(untitled) (New York, 1986)
The volume also includes a theoretical introduction which offers an original way of conceptualizing the interaction between culture and technology.
Keywords: Technology,Technology,Technology,Công nghệ,Công nghệ,Công nghệ; China,India,Japan,Trung Quốc,Ấn Độ,Nhật Bản